The factors forming investor's failure: Is financial literacy a matter? Viewing test by cognitive mapping technique - Amari Mouna; Jarboui Anis (Cogent Economics & Finance, 2015)
The objective of this paper is to apply cognitive map-related techniques to extract causal knowledge from a specific problem domain. This paper proposes to draw an average cognitive map in order to identify the failure factors of the Tunisian small investors. Our paper extends traditional and behavioral finance and previous research by proposing a new approach to building an average cognitive map for the explanation of small investors' failure in the stock market.
Keywords: 330; individual investor; failure; behavior; cognitive mapping